Efeito da estruturação de habitat por macrófitas aquáticas sobre atributos da assembleia de Chironomidae : uma análise experimental. - Bando, Fabielle Mucio (2016)
Structural heterogeneity in aquatic environments provided by aquatic macrophytes increases the habitat availability resulting in more resources available for plant-associated communities. Therefore, plant-associated organisms are strongly influenced by the structural heterogeneity. In this study, we carried out an experiment in the field, manipulating the structural heterogeneity of macrophytes beds, generating two treatments: (i) low structural heterogeneity (one biological types of macrophytes) and (ii) high structural heterogeneity (three biological types of macrophytes). Measuring the variation in community attributes of Chironomidae family organisms. Our main goal was identifying how the functional diversity responds to changes in the structural heterogeneity. We tested the hypothesis that (i) heterogeneous macrophyte beds increases the functional diversity Chironomidae assemblage and, (ii) species richness, species diversity and density respond to changes in structural heterogeneity. Functional richness (FRic), functional evenness (FEve) and functional divergence (FDiv) did not differ among treatments, suggesting that the structural heterogeneity does not affect the functional diversity of Chironomidae. The species richness and diversity of Shannon-Wiener also did not differ between treatments, indicating that the structural heterogeneity was not a structuring factor of Chironomidae assemblage. However, the density of Chironomidae assemblage was significantly higher density in the treatment with three biological types of macrophytes. Finally, our results indicate that habitat heterogeneity per se is not used as an indication of the possible diversity of aquatic animals plant-associated in littoral areas.